1992
DOI: 10.1055/s-2007-1021301
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Voluntary Exercise on Bone Growth and Calcium Metabolism in Spontaneously Hypertensive Rats

Abstract: The effects of voluntary exercise on bone length and calcium metabolism were investigated in spontaneously hypertensive rats (SHR) and Wistar rats. They were classified into voluntary exercise or sedentary group. Systolic blood pressure (SBP), bone length, urinary calcium excretion, plasma calcium and parathyroid hormone levels (PTH) were measured for analysis. SBP of the trained SHR (T-SHR) was significantly lower than that of the nontrained SHR (NT-SHR) at 10 and 11 weeks of age, but the trained Wistar rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Similarly, endurance running (Saville and White 1969;Shimegi et al 1990;Forwood and Parker 1991;Yeh et al 1993), wheel running (Leblance et al 1983Newhall et al 1991;Umemura et al 1992) and jump training (Umemura et al 1995) has been shown to increase bone mass in rats. In these animals, it has been found that bone remodelling imbalance spontaneously occurs with aging and after castration, because bone resorption then exceeds bone formation (Burr and Martin 1989).…”
Section: Introductionmentioning
confidence: 98%
“…Similarly, endurance running (Saville and White 1969;Shimegi et al 1990;Forwood and Parker 1991;Yeh et al 1993), wheel running (Leblance et al 1983Newhall et al 1991;Umemura et al 1992) and jump training (Umemura et al 1995) has been shown to increase bone mass in rats. In these animals, it has been found that bone remodelling imbalance spontaneously occurs with aging and after castration, because bone resorption then exceeds bone formation (Burr and Martin 1989).…”
Section: Introductionmentioning
confidence: 98%
“…Bone remodeling is controlled by both mechanical and hormonal factors (7,9). Moderate physical exercise such as voluntary and/or endurance run training (8,27,31,42), wheel running (19,20,35), swimming (32), and jump training (36) has been shown to increase bone mass in rats. However, intensive [80% of maximal O 2 consumption (V O 2 max ), 1 h/day, 5 days/wk for 11 wk] swimming (3) or treadmill running (2) leads to retarded longitudinal bone growth, architectural alteration, and osteoblastic impairment in the tibia of 3-wk-old male rats.…”
mentioning
confidence: 99%
“…In SHRs performing free running wheel exercise, trained SHRs had higher plasma PTH concentrations (Umemura et al. ). However, it is unlikely that high PTH directly reduces renal PTHR1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Again, a potential molecular mechanism has not been identified for either of the two mechanisms. In SHRs performing free running wheel exercise, trained SHRs had higher plasma PTH concentrations (Umemura et al 1992). However, it is unlikely that high PTH directly reduces renal PTHR1 expression.…”
Section: Discussionmentioning
confidence: 99%